TB Anywhere is TB Everywhere - Jonathan M. Wortham (Israel Journal of Health Policy Research, 2018)
Abstract To control and prevent outbreaks, public health programs in all countries, regardless of tuberculosis (TB) incidence, must maintain the capacity to perform core control and prevention activities. These include diagnosing and treating cases, contact investigations, and infection prevention and control activities. Congregate settings and healthcare facilities demand special attention, because of the potential for outbreaks associated with infectious cases in these settings. Since almost one-fourth of the world population is thought to be infected with Mycobacterium tuberculosis, enhanced efforts to diagnose and treat latent TB infection are needed to prevent future cases and accelerate progress towards TB elimination.